Salvia officinalis essential oil in bean weevil control - Scariot, Maurício Albertoni (2016)
Bean weevil [Acanthoscelides obtectus Say (Coleoptera: Bruchidae)] is considered the main storage pest of the bean crop. Its control is performed mainly by chemical treatment, which has potential to cause resistance in pests, as well as environmental contamination. This study aimed at evaluating the insecticidal and repellent effect of Salvia officinalis L. essential oil against bean weevil. The doses used for the insecticidal test were: 0 L t-1, 0.5 L t-1, 1.0 L t-1, 1.5 L t-1, 2.5 L t-1 and 5.0 L t-1 of bean grains. For the mortality test, the experimental design was completely randomized, in a 6 × 7 (dose × time) factorial scheme, with five replications. The number of dead insects was counted at 2, 6, 12, 24, 48, 72 and 96 h after the insect introduction. The repellency test was conducted in arenas, under a completely randomized design, using the same doses applied to evaluate the insecticidal effect. Counts were performed 24 h after the introduction of insects. The insecticidal effect of the S. officinalis essential oil on A. obtectus resulted in mortality rates higher than 95 %, after 6 h of insect introduction, for all doses tested.  Repellency effect was also detected for all doses tested.